The cross technique for the positioning of Kerboull plate in acetabular reconstruction surgery - Assi, Chahine (2018)
Acetabular reconstruction aims at filling bony defects and positioning the acetabular component in its anatomical place. To this, the use of Kerboull plate would give an automatic optimal positioning while reconstructing the acetabular cavity. We developed a technique, the cross technique, that approaches acetabular reconstruction in a systematic way. It consists of placing the KP following its cross design, in reference to a vertical plane (hook, center, palette) and a horizontal plane (horizontal flanges). The cross technique has three steps; the preparation of the acetabular cavity, the cross technique itself and cementation. We recommend a downsizing of the plate in relation to the size of the acetabular cavity in addition to another downsizing of the acetabular implant in relation to the plate size whenever a dual mobility cup is used.